Analisis Pengaruh Variabel Makro Ekonomi terhadap Nilai Aktiva Bersih Reksadana Saham Syariah Periode 2015-2019 - Hani Nurrahmawati; Hasbi Assidiki Mauluddi; Endang Hatma Juniwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The title of this research is Analysis Influence of Macroeconomic to Net Asset Value of Islamic Mutual Fund Equity period 2015-2019. The purpose of this study is to determine the effect of partially and simultaneously variables of BI Rate, Inflation, Composite Stock Price Index and Exchange Rate on Net Asset Value of Sharia Mutual Funds in Indonesia in the period January 2015 - December 2019. The dependent variable is Net Asset Value of Sharia Mutual Funds, while the independent variables are BI Rate, Inflation, Composite Stock Price Index and Exchange Rate.Types of data used in this study are secondary data sourced from OJK, IHSG-IDX and BI published between 2015-2019. All of the data will be processed panel data which is a combination of time series data and cross section data. The results of this research showed that in the partial just variables of the BI Rate, Inflation, Composite Stock Price Index and Exchange Rate influenced to Net Assets Value of Islamic Mutual Funds in Indonesia, and simultaneous from variables of the BI Rate, Inflation, Composite Stock Price Index and Exchange Rate influenced to Net Assets Value of Islamic Mutual Funds in Indonesia and the value of Adjusted R-square coefficient of determination is 0.311175 means in togetherness variables of the BI Rate, Inflation, Composite Stock Price Index and Exchange Rate have a contribution influenced NAV of Islamic Mutual Funds in the amount of 31%, while the rest is 69% influenced by other variables that are not included into this research.